2016
DOI: 10.1155/2016/7479357
|View full text |Cite
|
Sign up to set email alerts
|

Women in Saudi Arabia and the Prevalence of Cardiovascular Risk Factors: A Systematic Review

Abstract: Background. Cardiovascular disease (CVD) is one of the leading causes of death in Saudi Arabia. Saudi women in particular are more susceptible as there are sociocultural restrictions on female physical activities that may lead to high prevalence of CVD risks, especially obesity, and physical inactivity. This study aims to systematically review the published articles related to the prevalence of CVD risk among women in Saudi Arabia. The search strategy covers all published articles that assess the risk factor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 77 publications
4
54
2
Order By: Relevance
“…The susceptibility of Saudi women to high rates of GDM may be related to the cultural restrictions on female physical activities that may lead to physical inactivity and increased access to fast foods, both causing obesity. A recent review has shown high prevalence among Saudi women of smoking (up to 9%), hypertension (22%), diabetes (up to 27.6%), overweight (27%), and obesity (40%), and physical inactivity (53.2% to 98.1%), hypercholesterolemia (24.5%) and metabolic syndrome (MetS) (up to 40.3%) [ 36 ]. MetS is a cluster of established risk factors that together increase predisposition to major chronic diseases such as heart diseases and diabetes mellitus and a recent study (2014) on adults from several regions of Saudi Arabia confirmed > 28% incidence of MetS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of Saudi women to high rates of GDM may be related to the cultural restrictions on female physical activities that may lead to physical inactivity and increased access to fast foods, both causing obesity. A recent review has shown high prevalence among Saudi women of smoking (up to 9%), hypertension (22%), diabetes (up to 27.6%), overweight (27%), and obesity (40%), and physical inactivity (53.2% to 98.1%), hypercholesterolemia (24.5%) and metabolic syndrome (MetS) (up to 40.3%) [ 36 ]. MetS is a cluster of established risk factors that together increase predisposition to major chronic diseases such as heart diseases and diabetes mellitus and a recent study (2014) on adults from several regions of Saudi Arabia confirmed > 28% incidence of MetS [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Kingdom of Saudi Arabia is a rapidly developing country with improvements in living standards and changing social practices that contribute to recent increases in heart disease and associated chronic illnesses (Alshaikh, Filippidis, Baldove, Majeed, & Rawaf, ). Hypertension is a common chronic condition in the country, with men being at greater risk than women.…”
Section: Introductionmentioning
confidence: 99%
“…These risk factors such as diabetes (DM), hypertension (HTN), smoking, obesity, hypercholesterolemia, metabolic syndrome (MetS) and physical inactivity are modifiable lifestylerelated concerns that have significant consequences to the health of Saudi women [2][3][4][5]. Three studies (two systematic and one cohort) published in the course of the development of this research confirmed and highlighted the high prevalence of these CVD risks not only for Saudi women, but also for women in other member countries of Gulf Cooperation Council (GCC) [6][7][8].…”
Section: Introductionmentioning
confidence: 56%